Review of Nikolaos Papadogiannis’, Militant around the Clock? Left-Wing Youth Politics, Leisure, and Sexuality in Post-Dictatorship Greece, 1974–1981 - Kornetis, Kostis (Historein, 2017)
Nikolaos Papadogiannis. Militant around the Clock? Left-Wing Youth Politics, Leisure, and Sexuality in Post-Dictatorship Greece, 1974–1981. New York: Berghahn, 2015. x + 329 pp.